Chemical Analysis and Antioxidant Activities of Resin Fractions from Pistacia lentiscus L. var. Chia in Neuroblastoma SH-SY5Y Cells - Achilleas Georgantopoulos; Foteini D. Kalousi; Federica Pollastro; Ioannis Tsialtas; Natasa P. Kalogiouri; Anna-Maria G. Psarra (Molecules, 2025)
Chios mastiha is the natural aromatic resin of Pistacia lentiscus L. var. Chia, Anacardiaceae, which is exclusively cultivated in the southern part of the Greek island of Chios. Chios mastiha (P. lenticonus/Chios mastiha) is well-known for its distinctive taste and aroma and has been known since ancient times due to its healing properties in gastrointestinal and inflammatory disorders and because of its anti-bacterial and anti-fungal activities. In this study, the chemical composition, applying LC-QTOF-MS/MS analysis, and the antioxidant activities of three different polarity P. lenticonus/Chios mastiha fractions, apolar, medium polar, and polar, were characterized in human neuroblastoma SH-SY5Y cells. Chemical analysis of the fractions unveiled new components of P. lenticonus/Chios mastiha, mainly fatty acids compounds, known for their antioxidant activity and regulatory effects on lipid metabolism. By applying the MTT assay and confocal microscopy analysis, we showed that P. lenticonus/Chios mastiha fractions, especially the apolar and medium polar fractions, enriched in triterpenes and fatty acids, caused suppression of the H2O2-induced reduction in cell viability, ROS production, and depolarization of the mitochondrial membrane potential, in SH-SY5Y cells. Moreover, Western blot analysis revealed that apolar fraction, enriched in fatty acids, induced expression of the PPARα, which is well-known for its antioxidant activities and its crucial role in lipid metabolism. Induction of PPARα, a GR target gene, was also accompanied by an increase in GR protein levels. Enhanced antioxidant activities of the apolar fraction may be correlated with its chemical composition, enriched in fatty acids and triterpenoids. Thus, our results indicate the neuroprotective actions of P. lenticonus/Chios mastiha fractions, highlighting their potential application as neuroprotective agents in neurodegenerative diseases.